Про крошку-Дракошку: [стихи : книга на картоне] / Андрей Усачев ;[ художники: И. Бордюг, Н. Трепенок] - Усачев Андрей Алексеевич (АСТ, 2006)
Экземпляры: ф.15 (20170801) / Инвентарный номер: zzzzz / Цена: 20.00 / Сис.шифр: Д / Авт.знак: У 74 / ГРНТИ: 17.82.93 / ББК: Д